Populist leaders and the economy - Manuel Funke; Moritz Schularick; Christoph Trebesch (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2020)
Populism at the country level is at an all-time high, with more than 25% of nations currently governed by populists. How do economies perform under populist leaders? We build a new cross-country database identifying 50 populist presidents and prime ministers 1900-2018. We find that the economic cost of populism is high. After 15 years, GDP per capita is more than 10% lower compared to a plausible non-populist counterfactual. Rising economic nationalism and protectionism, unsustainable macroeconomic policies, and institutional decay under populist rule do lasting damage to the economy.
Keywords: 330; Populismus; Staatsoberhaupt; Protektionismus; Wirtschaftlicher Schaden; Wirkungsanalyse